DETERMINAN KINERJA PENGELOLAAN KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI (Studi Pada SKPK di Kota Langsa) - Armita; Afrah Junita; Muhammad Salman (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
The purpose of this study was to determine the effect of Financial Management Competence and Work Experience on Financial Management Performance with Organizational Commitment as Moderating on SKPK in Langsa City. This study uses quantitative methods. The population in this study were all 30 SKPKs in Langsa City. All SKPKs were sampled with 3 (three) respondents in each SKPK with a total of 90 respondents. Data was collected by distributing questionnaires and by using measuring instruments in the form of validity and reliability tests. The analytical method used is Moderated Regression Analysis (MRA). The results of the study found that partially financial management competence had no effect on financial management performance, work experience and organizational commitment had a significant positive effect on financial management performance, organizational commitment weakened the relationship between financial management competence and financial management performance, organizational commitment strengthened the relationship between work experience and financial management performance. This study has limitations that can be considered for future researchers in order to improve further research. The limitation of this research is that the researcher cannot provide questionnaires directly to several respondents and assists the respondents in filling out the questionnaires. This is due to the busyness of the respondents. Some respondents could hardly afford to answer the questionnaire directly and asked for up to one week. This constraint makes it impossible to know whether the respondents actually filled out the questionnaire properly. Also, the researcher cannot directly answer things that are not known by the respondents regarding the questions asked in the questionnaire. So it is suggested that further researchers can distribute questionnaires directly and explain a little about the research variables so that respondents can ask about things that are not known and can understand the intent of the questionnaire questions